Association between Gender and Utilization of Cataract Surgical Services: A Systematic Review and Meta-Analysis - Farisa Shauma Fachir; Syamsul Arifin; Silvia Kristanti Tri Febriana; Adi Nugroho; Iwan Aflanie; Tenri Ashari Wanahari (Sriwijaya Journal of Ophthalmology, 2023)
Introduction: Cataract is the most prevalent cause of blindness worldwide, which can be effectively treated with surgery. The high incidence of blindness in women highlights the need to address gender inequality in the utilization of cataract surgery. This study aimed to assess the association between gender and the utilization of cataract surgical services. Methods: A systematic review and meta-analysis were conducted according to preferred reporting items for systematic review and meta-analysis (PRISMA) guidelines. A literature search was performed on PubMed and ProQuest in the last 10 years (2012 to 2022). The search strategy used the following terms: ("cataract surgical" or "cataract surgical coverage" or "cataract surgical uptake") and ("sex" or "gender"). Data were analyzed in RevMan 5.3, with pooled effect estimates reported as OR with a 95% confidence interval (CI). Results: A total of 13 articles were identified and included in the meta-analysis. The pooled results of these studies indicate a statistically significant association between gender and the utilization of cataract surgery, with a lower utilization probability, observed among women compared to men (OR 0.76, 95% CI 0.60-0.98, p=0.03). High heterogeneity was observed among studies (I2 89%, p<0.0001). Conclusion: There is an association between gender and the utilization of cataract surgical services, with women being less likely than men to use cataract surgical services.